Flow states and transitions of an active nematic in a three-dimensional channel - Chandragiri, S; Doostmohammadi, A; Yeomans, JM; Thampi, SP (American Physical Society, 2020)
We use active nematohydrodynamics to study the flow of an active fluid in a 3D microchannel, finding a transition between active turbulence and regimes where there is a net flow along the channel. We show that the net flow is only possible if the active nematic is flow aligning and that, in agreement with experiments, the appearance of the net flow depends on the aspect ratio of the channel cross section. We explain our results in terms of when the hydrodynamic screening due to the channel walls allows the emergence of vortex rolls across the channel.